Book Review Letter of the Law, Alan Edward Nourse, Publisher Library of Alexandria, 2000, ISBN 1492373567 - Lestari, Liza Winda (Faculty of Law Universitas Negeri Semarang, 2021)
This book telling about a clever man named Zeckler came to a very backward and primitive country. This country is located far from the place of origin, initially came to this country to develop business and do business with local residents. The people there live as farmers and get food from the agricultural produce. So in that country, land is more important than money. Because soil is the key to life. But in the fact that Zeckler is a clever cheater, he is very interested. One day this man committed fraud and traded land illegally, he also stole some local residents, the theft was carried out by violence.